Exact observability and controllability for a nonsimple elastic rod. Issue 9 (4th July 2019) - Aouadi, Moncef; Kassraoui, Jihed
ABSTRACT: In this paper, we prove exact observability, boundary and internal exact controllability results for a nonsimple elastic rod. By the spectral analysis method, it is shown that the considered problem has a sequence of eigenfunctions, which forms a Riesz basis for the state space. The exact observability is proved by application of a modified version of Ingham's Theorem. Then, via the Hilbert Uniqueness method, we prove a boundary controllability result with only one controller and an internal controllability result.